"I did not see a need to get tested before, everything was going well with my health": a qualitative study of HIV-testing decision-making in KwaZulu-Natal, South Africa. Issue 1 (2nd January 2018) - Tariq, Shema; Hoffman, Susie; Ramjee, Gita; Mantell, Joanne E.; Phillip, Jessica L.; Blanchard, Kelly; Lince-Deroche, Naomi; Exner, Theresa M.
ABSTRACT: Few studies have examined HIV-testing decision-making since the South African national HIV counseling and testing campaign in 2010–2011 and subsequent expansion in antiretroviral therapy (ART) eligibility in 2012. We describe HIV-testing decision-making and pathways to testing among participants in Pathways to Care, a cohort study of newly-diagnosed HIV-positive adults in KwaZulu-Natal. Our analysis is embedded within a theoretical framework informed by Arthur Kleinman's work on pluralistic healthcare systems, and the concept of diagnostic itineraries (i.e., the route taken to HIV testing). We conducted 26 semi-structured interviews in 2012, within one month of participants' diagnosis. Most ( n = 22) deferred testing until they had developed symptoms, and then often sought recourse in non-biomedical settings. Of the eleven symptomatic participants who accessed professional medical services prior to testing, only three reported that a healthcare professional had offered or recommended an HIV test. Although ART emerged as an important motivator, offering hope of health and normalcy, fear of death and HIV-related stigma remained key barriers. Despite national policy changes in testing and treatment, health system and individual factors contributed to ongoing high levels of late diagnosis of HIV in this study population. Encouraging local health systems to direct clients toward HIV testing, and continuing to raise awareness of the benefits of routine testing remain important strategies to reduce delayed diagnoses.